Travify - Itinerary Management System - Mohd Rasidi, Muhammad Hakimie Ikhwan; Mohamed Khairi, Muhammad Syafiq Syahmi; Md Khairi, Muhammad Syazwan Amri; Mohamad Madon, Mizani (Multidisciplinary Applied Research and Innovation, 2026)
The objective of this project is to develop a smart itinerary planning system called Travify to assist users in managing their travel plans in a centralized platform. Many users face challenges using multiple tools like notes, calendars, and maps to organize trips, which often leads to disorganization and missed details. Travify solves this by offering key features such as itinerary creation, budget tracking, destination management, and profile customization. The system uses real-time APIs, user-generated content, and cloud integration for better performance and accessibility. Travify was developed using the Agile methodology, involving iterative development cycles and regular feedback loops to ensure continuous improvement. The front end was built using HTML, CSS, and JavaScript, while the backend was implemented with PHP and a MySQL database for data management. Functionality was validated through unit testing, integration testing, and user testing. Feedback from testing revealed improved usability and convenience. Travify aims to simplify planning, enhance personalization, and ensure a seamless travel experience for all users.